PEMBANGUNAN HUKUM: PENERAPAN GANTI KERUGIAN PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Situmorang, Torang; Hasugian, Evalina Elisabeth; Pasaribu, Rosma Mediana (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Implementation of development for the public interest ultimately leads to land acquisition for the publicinterest. Suppose you need a large amount of land. Its implementation needs to be carried out quicklyand transparently by taking into account the principle of respect for legal rights to land. This paperuses a normative juridical method, namely the statutory regulation approach. Government RegulationNumber 30 of 2017 concerning the third amendment to Government regulation number 15 of 2005concerning Toll Roads. Presidential Regulation No. 65 of 2006 concerning Amendment to PresidentialDecree No. 36 of 2005 concerning Land Acquisition for Implementation of Development in the PublicInterest. Regulation of the President of the Republic of Indonesia Number 71 of 2012 concerningImplementation of Land Acquisition for Development in the Public Interest. Regulation of the Presidentof the Republic of Indonesia Number 148 of 2015 concerning the Fourth Amendment to Regulation ofthe President of the Republic of Indonesia Number 71 of 2012 concerning Implementation of LandAcquisition for Development in the Public Interest. Regulation of the President of the Republic ofIndonesia Number 19 of 2021 concerning Implementation of Land Acquisition for Development in thePublic Interest. Supreme Court Regulation Number 3 of 2016 concerning Procedures for SubmittingObjections in Custody of Compensation to the District Court in Land Procurement for Development inthe Public Interest. This paper gets the result that when the community has to relinquish land in a landacquisition project, these values will disappear and only be replaced with monetary values that can beused up in a short period of time. The theory of justice in the case of decision No. 50/Pdt/PN nocompensation was received for the land affected by the construction of the toll road on the KisaranTebing Tinggi Phase I Road Kuala Tanjung-Tebing Tinggi Section in Serdang Bedagai Regency.